Financial Information Quality And Investment Efficiency: Evidence From Malaysia - Ebrahimi Rad, Seyed Sajad; Embong, Zaini; Mohd Saleh , Norman; Jaffar, Romlah (Asian Academy of Management (AAM), 2016)
This study aims to empirically examine the association between financial information quality and investment efficiency among firms in Malaysia. Sample of this study consists of 558 firms listed on the Main Board of Bursa Malaysia from the year of 2001 until 2011. The investment efficiency is measured based on firms’ deviations from the expected investment level. The financial information quality is measured based on four different measurement schemes. The results provide support that financial information quality is significantly positively related to investment efficiency. The inclusion of several firm level control variables and use of alternative models to measure investment efficiency provides consistent findings. The results of this study provide further understanding and empirical evidence relevant to quality of financial information and investment efficiency. As most of the extant studies on this association have been done on data from the US and advanced countries, this study fills the gap in literature by investigating the impact of financial information quality on investment efficiency in an emerging market. Although emerging markets make up the vast majority of economic activity around the world, they have received limited attention in academic research. Findings of this study could be of interest to the international organisations such as World Bank whose missions are to aid countries with developing and transitional economy, and improve living conditions of their citizens.